MANAGEMENT OF GERIATRIC PATIENTS SUFFERRING FROM CHRONIC CONSTIPATION - Yu. S. KOKAREV (Кубанский научный медицинский вестник, 2018)
The article discusses diagnosis and differential diagnosis of primary and secondary constipation in elderly patients. The analysis of possible options of constipation treatment is made on the basis of the evidence-based medicine criteria and the use of the most effective laxatives.